2021
DOI: 10.3390/vaccines9050470
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric RHDV Virus-Like Particles Displaying Foot-and-Mouth Disease Virus Epitopes Elicit Neutralizing Antibodies and Confer Partial Protection in Pigs

Abstract: Currently there is a clear trend towards the establishment of virus-like particles (VLPs) as a powerful tool for vaccine development. VLPs are tunable nanoparticles that can be engineered to be used as platforms for multimeric display of foreign antigens. We have previously reported that VLPs derived from rabbit hemorrhagic disease virus (RHDV) constitute an excellent vaccine vector, capable of inducing specific protective immune responses against inserted heterologous T-cytotoxic and B-cell epitopes. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Because 1C9 is directed against a conformational epitope affected by insertion of chimeric sequences into the exposed VP60 loop [ 38 ], we interpret this result to show that insertion of both the control and the relevant epitopes occurred as expected. Altogether, these results extend previous reports [ 10 , 13 ] to show insertion of a new antigenic peptide at the exposed loop of RHDV VP60 for the generation of chimeric VLPs and confirms the FMDV serotype C specificity of these novel particles.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Because 1C9 is directed against a conformational epitope affected by insertion of chimeric sequences into the exposed VP60 loop [ 38 ], we interpret this result to show that insertion of both the control and the relevant epitopes occurred as expected. Altogether, these results extend previous reports [ 10 , 13 ] to show insertion of a new antigenic peptide at the exposed loop of RHDV VP60 for the generation of chimeric VLPs and confirms the FMDV serotype C specificity of these novel particles.…”
Section: Resultssupporting
confidence: 91%
“…We recently reported that a chimeric RHDV VLP vaccine candidate containing the FMDV B-cell epitope from O UK/01 serotype as immunogen induces a potent humoral response both in murine and porcine models. Further, vaccination of pigs induced high titers of neutralizing antibodies and conferred partial protection upon homologous challenge [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations